2003
DOI: 10.1242/jeb.00609
|View full text |Cite
|
Sign up to set email alerts
|

Towards genetic manipulation of wild mosquito populations to combat malaria: advances and challenges

Abstract: SUMMARYMalaria kills millions of people every year, yet there has been little progress in controlling this disease. For transmission to occur, the malaria parasite has to complete a complex developmental cycle in the mosquito. The mosquito is therefore a potential weak link in malaria transmission, and generating mosquito populations that are refractory to the parasite is a potential means of controlling the disease. There has been considerable progress over the last decade towards developing the tools for cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 47 publications
0
47
0
2
Order By: Relevance
“…They have been studied mainly in connection with the transmission of tropical diseases, such as malaria and yellow fever (Dekker et al, 2005;Riehle et al, 2003). To suck blood from a host through a long and slender proboscis, female mosquitoes utilize pumping organs located in their head.…”
Section: Introductionmentioning
confidence: 99%
“…They have been studied mainly in connection with the transmission of tropical diseases, such as malaria and yellow fever (Dekker et al, 2005;Riehle et al, 2003). To suck blood from a host through a long and slender proboscis, female mosquitoes utilize pumping organs located in their head.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae s.s. Giles and its sibling species An. arabiensis Patton, because little is known about the biology of this sex , and because these species are the most important vectors of malaria in Africa (Gillies and DeMeillon, 1968;White, 1974) and thus a leading target for control measures based on the release of genetically modified (Ito et al, 2002;Riehle et al, 2003) and/or sterile males (Helinski et al, 2006a). Consequently there is an urgent need to understand the life history and performance of free-living male An.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on the fitness of transgenic mosquitoes, including measurements of longevity and fertility and use of population cages, has been performed. Most of these studies (Riehle et al 2003, Marrelli et al 2006a, showed a reduced fitness load of transgenic mosquitoes, when compared to the wild population. Only one transgene, the peptide SM1 expressed in An.…”
Section: Several Tasks Need To Be Solved Before a Trans-genic Mosquitmentioning
confidence: 99%
“…This latter aspect is of practical importance because in such cases the transgene(s) can be driven through a population only once (Riehle et al 2003).…”
Section: Several Tasks Need To Be Solved Before a Trans-genic Mosquitmentioning
confidence: 99%